Alcohol Intake and Weight Loss During Intensive Lifestyle Intervention for Adults with Overweight or Obesity and Diabetes. Issue 1 (13th November 2018) - Chao, Ariana M.; Wadden, Thomas A.; Tronieri, Jena Shaw; Berkowitz, Robert I.
Abstract : Objective: This study aimed to assess whether alcohol consumption decreases during an intensive lifestyle intervention (ILI) and whether alcohol consumption is associated with weight loss among participants with overweight or obesity and type 2 diabetes. Methods: Participants ( n = 4, 901) were from the Action for Health in Diabetes (Look AHEAD) study, a randomized controlled trial that compared an ILI with a diabetes support and education (DSE) control. Mixed‐effects models were used to estimate the effect of the ILI on alcohol consumption and the influence of alcohol consumption on weight loss at year 4. Results: ILI and DSE participants did not differ in changes in alcohol consumption. Alcohol intake was not associated with weight loss at year 1 of the ILI. ILI participants who abstained from alcohol lost 5.1% ± 0.3% of initial weight at year 4 compared with a significantly ( P = 0.04) smaller 2.4% ± 1.3% for consistent heavy drinkers. ILI participants who abstained from alcohol consumption over the 4 years lost 1.6% ± 0.5% more weight relative to individuals who drank alcohol at any time during the intervention ( P = 0.003). DSE participants did not differ in weight loss by alcohol consumption. Conclusions: Heavy alcohol drinkers are at risk for suboptimal long‐term weight loss. Decreasing alcohol consumption may improve weight management among individuals with diabetes.